2006
DOI: 10.1051/0004-6361:20064907
|View full text |Cite
|
Sign up to set email alerts
|

Dust distributions in debris disks: effects of gravity, radiation pressure and collisions

Abstract: We model a typical debris disk, treated as an idealized ensemble of dust particles, exposed to stellar gravity and direct radiation pressure and experiencing fragmenting collisions. Applying the kinetic method of statistical physics, written in orbital elements, we calculate size and spatial distibutions expected in a steady-state disk, investigate timescales needed to reach the steady state, and calculate mass loss rates. Particular numerical examples are given for the debris disk around Vega. The disk should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
310
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(323 citation statements)
references
References 48 publications
12
310
0
1
Order By: Relevance
“…Such a radial profile that rises outward with a sharp outer edge contrasts with those derived for the archetypal disks Vega (Su et al 2005;Krivov et al 2006;Müller et al 2010;Sibthorpe et al 2010) and β Pictoris (Golimowski et al 2006;Thébault & Wu 2008;Krivov et al 2009;Vandenbussche et al 2010). In these disks, the derived geometrical optical thickness typically falls off with a moderate r −1.5 relationship beyond the peak value, i.e.…”
Section: Resultsmentioning
confidence: 66%
“…Such a radial profile that rises outward with a sharp outer edge contrasts with those derived for the archetypal disks Vega (Su et al 2005;Krivov et al 2006;Müller et al 2010;Sibthorpe et al 2010) and β Pictoris (Golimowski et al 2006;Thébault & Wu 2008;Krivov et al 2009;Vandenbussche et al 2010). In these disks, the derived geometrical optical thickness typically falls off with a moderate r −1.5 relationship beyond the peak value, i.e.…”
Section: Resultsmentioning
confidence: 66%
“…This is clearly not the case for a Dohnanyi size distribution with dN ∝ s −3.5 ds, as well as for most of the more realistic "wavy" distributions derived from collisional evolution models (e.g., Krivov et al 2006;Thébault & Augereau 2007). However, there is a range of systems for which these numerical studies have shown that they could be depleted of small grains, i.e., those with very low dynamical excitation e dyn .…”
Section: The "Natural" Thickness Of Debris Discsmentioning
confidence: 94%
“…Numerical studies of debris discs fall into two main categories: those investigating the collisional and size distribution evolution of the system are usually statistical particle-in-the-box models, of no or poor spatial resolution and very limited dynamical evolution (e.g., Krivov et al 2006;Thébault & Augereau 2007;Löhne et al 2008), while those studying the dynamics and the formation and evolution of spatial structures are mostly N-body type codes, where size distributions and mutual collisions are usually neglected (see for example Reche et al 2008).…”
Section: Modelmentioning
confidence: 99%
“…With such data, any deviation from the theoretical power law size distribution of observable dust, e.g. the "wavy" size distribution predicted from numerical models of collisional processes in debris disks (Thébault & Augereau 2007;Krivov et al 2006), can be thoroughly investigated. In addition, ALMA will enable detection and imaging of many faint disks, and permit detailed SED modelling of the very coldest Kuiper-belt systems.…”
Section: Spectral Energy Distributionsmentioning
confidence: 99%